2022
DOI: 10.1186/s41983-022-00483-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin B12 level and clinical peripheral neuropathy in type 2 diabetic patients on metformin therapy

Abstract: Background Vitamin B12 malabsorption is one of the side effects of long-term metformin intake. Prolonged vitamin B12 deficiency can lead to irreversible nervous system damage. So, the current study aimed to determine the association between serum vitamin B12 level and clinical peripheral neuropathy among type 2 DM patients who are on metformin in comparison to those not taking it. It is a cross-sectional study that was conducted in Egypt and recruited 100 type 2 diabetic patients who were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Although VB12 is an important factor for neurological functioning, the association between low VB12 and neuropathy was not evident in our research. A study conducted in Egypt reported similar ndings 25 . This could be elucidated by the early detection and treatment of VB12 de ciency in the pre-clinical stage and the overall low prevalence of neuropathy among the cohort.…”
Section: Discussionsupporting
confidence: 60%
“…Although VB12 is an important factor for neurological functioning, the association between low VB12 and neuropathy was not evident in our research. A study conducted in Egypt reported similar ndings 25 . This could be elucidated by the early detection and treatment of VB12 de ciency in the pre-clinical stage and the overall low prevalence of neuropathy among the cohort.…”
Section: Discussionsupporting
confidence: 60%
“…After removing duplicates, we reviewed the titles and abstracts of 1598 articles and identified 180 possible eligible studies for full-text screening. Among all the eligible studies, 17 were included in the current meta-analysis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Among all the included studies, 13 were cross-sectional studies, 3 were retrospective cohorts, and 1 was a case-control study.…”
Section: Resultsmentioning
confidence: 99%
“…FIGURE 2: Forest plot showing the association of metformin with vitamin B12 deficiencySources: References[12,14,16,21,23,[25][26] …”
mentioning
confidence: 99%
“…Contrary to initial disappointing results, Russo et al mentioned that in type 2 DM patients who received Metformin for at least 6 months, vitamin B12 deficiency was just mild and didn't have a relationship with developing diabetic neuropathy [76]. Fakkar et al confirmed the previous study and mentioned that despite the lower levels of vit B12 in Metformin recipients, it is not associated with higher incidence of developing PN [77]. The last systematic review published in could not analyze the effect of Metformin on PN in diabetic patients due to the lack of data [78].…”
Section: Possible Resolutions For the Treatment Of Pnmentioning
confidence: 92%